(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This paper deals with the analysis of one of the most sig- nificant incidents of the sugar cane cutters march: the poli- ce repression that occurred during the 7th May 1964. The main objective is to analyze the construction of personal na- rratives from photographs. The article is based on the pre- sentation of two types of materials. First, it shows the photo- graphs published the day after the events by the newspaper El Popular and, second, it exposes the memories of the main players. Particularly, the text makes focus on the narratives of the members of the Unión de Trabajadores Azucareros de Artigas (UTAA) and the photographer. The paper conclu- des by pointing out the importance of the contribution of graphic material for the reconstruction of the personal sto- ries of those involved as well as the collective memory of rural workers in Uruguay.